2014
DOI: 10.1038/ncomms5279
|View full text |Cite
|
Sign up to set email alerts
|

Engineering interlocking DNA rings with weak physical interactions

Abstract: Catenanes are intriguing molecular assemblies for engineering unique molecular devices. The resident rings of a catenane are expected to execute unhindered rotation around each other, and to do so, they must have weak physical interactions with each other. Due to sequence programmability, DNA has become a popular material for nanoscale object engineering. However, current DNA catenanes, particularly in the single-stranded (ss) form, are synthesized through the formation of a linking duplex, which makes them le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 33 publications
(49 reference statements)
0
38
0
Order By: Relevance
“…Recently, 168 and 128 bp dsDNA catenanes have been fabricated . Examples of ssDNA catenanes include catenated scaffolds for enzymes, interlocking DNA rings, Seeman's cube, in which two or more ssDNA rings are intertwined. Catenanes can be used to construct molecular machine.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, 168 and 128 bp dsDNA catenanes have been fabricated . Examples of ssDNA catenanes include catenated scaffolds for enzymes, interlocking DNA rings, Seeman's cube, in which two or more ssDNA rings are intertwined. Catenanes can be used to construct molecular machine.…”
Section: Methodsmentioning
confidence: 99%
“…To create DNA catenanes having weak physical interactions between each other, Li et al. adopted a random library approach to generate two‐ring DNA catenanes without a linking duplex (Figure D) . The weak physical interactions and capability of operating as independent units of the representative catenanes were signified by double‐stranded catenane synthesis, DNA hybridization, and rolling circle amplification experiments.…”
Section: Artificial Cnasmentioning
confidence: 99%
“…Template‐mediated enzymatic ligation could also be used to produce topologically linked ring structures known as catenanes. For example, DNA ligation reactions can be used to synthesize single‐stranded DNA catenanes with 2 or more component rings, including the ones with weak physical interactions between resident rings . They can also be used to prepare double‐stranded circular DNAs with excellent rigidity as components of nanodevices …”
Section: Introductionmentioning
confidence: 99%
“…By taking an in vitro selection approach, we have recently derived a number of DNA sequences from a random pool of DNAs that are able to form DNA [2]catenanes (D2Cs; two interlocked DNA rings) with a premade ssDNA circle without requiring the formation of a strong linking duplex . We have further shown that the constituent rings within these catenanes have minimal physical interactions .…”
Section: Figurementioning
confidence: 99%
“…By taking an in vitro selection approach, we have recently derived a number of DNA sequences from a random pool of DNAs that are able to form DNA [2]catenanes (D2Cs; two interlocked DNA rings) with a premade ssDNA circle without requiring the formation of a strong linking duplex . We have further shown that the constituent rings within these catenanes have minimal physical interactions . As we show in this work, the weak physical interactions between component rings of these D2Cs also make it possible to fabricate even more complex nanostructures such as DNA [3]catenanes (D3Cs; three interlocked DNA rings) consisting of a central mother ring and two identical or fraternal twin daughter rings: unusual nanostructures that have never been reported before.…”
Section: Figurementioning
confidence: 99%